읽기장애아동을 위한 하이브리드 모바일 읽기 게임의 사용성 검사 - 신미경(Mikyung Shin); 박은혜(Eunhye Park); 홍기형(Ki-Hyung Hong); 이주현(Joohyun Lee); 박혜원(Hyewon Park) (한국콘텐츠학회 논문지, 18(1), 2018)
The purpose of this study was to evaluate the usability of a hybrid mobile reading game among 14 parents of children with reading disabilities. The reading game consisted of six steps according to the process of reading (familiarizing with consonants and vowels, acquiring whole words, combining consonants and vowels, reading words, phonological rules, reading fluency). In this study, parents experienced steps one through three of the reading-game app and evaluated the general design features and Universal Design for Learning on a five-point scale. Regarding the general design features, parents rated usability (18 items in total) as high in the following order: interactive design, instructional design, and interface design. Regarding the Universal Design for Learning (9 items in total), parents evaluated usability as high in the following order: providing multiple means of representation, providing multiple means of action and expression, and providing multiple means of engagement. Lastly, suggestions for the improvement of the app, practical implications, and suggestions for future research are discussed. 본 연구의 목적은 14명의 읽기장애아동 부모를 대상으로 하이브리드 모바일 읽기 게임의 사용성에 대하여 평가한 것이다. 읽기 게임은 아동의 읽기 발달 과정에 따라 총 6단계(자모음 익숙해지기, 통글자 익히기, 자모음 결합하기, 단어 읽기, 음운 규칙, 읽기 자동화)로 구성되었다. 본 사용성 검사에서는, 부모들이 1단계부터 3단계의 읽기 게임 앱 내용을 경험해보고, 일반적인 디자인 설계 및 보편적 학습설계를 5점 평정척도로 평가하였다. 일반적인 디자인에 대한 사용성 검사 결과(총 18개 항목)를 살펴보면 상호작용 설계, 교수적 설계, 인터페이스 설계 순으로 높게 평가되었다. 보편적 학습설계 측면(총 9개 항목)의 검사 결과로는 다양한 방식의 표상을 제공, 다양한 방식의 행동과 표현수단을 제공, 다양한 방식의 학습 참여를 제공하는 것 순으로 사용성이 높게 평가되었다. 마지막으로 앱의 개선점, 현장에 제공하는 시사점, 미래연구를 위한 제언들이 논의되었다.